Articulatory Changes Following Treatment of Muscle Tension Dysphonia: Preliminary Acoustic Evidence. - Dromey, Christopher; Nissen, Shawn L.; Roy, Nelson; Merrill, Ray M. (Journal of Speech, Language & Hearing Research, 2008)
Purpose: Primary muscle tension dysphonia (MTD), a voice disturbance that occurs in the absence of structural or neurological pathology, may respond to manual circumlaryngeal techniques, which ostensibly alter the posture of the larynx and/or the configuration of the vocal folds without directly targeting supralaryngeal articulatory structures. Although the phonatory benefits of these techniques have been documented previously, this investigation examined whether acoustic evidence exists for articulatory changes accompanying successful management. Method: In this retrospective study of a clinical database, pre- and post-treatment speech samples from 111 women with MTD were analyzed for acoustic evidence of supraglottal vocal tract changes associated with voice improvement, which was confirmed by perceptual ratings of dysphonia severity. The slopes of the first and second formants in diphthongs, as well as global measures of speech timing were acquired. Twenty younger females with normal voices were recorded twice, across a similar time-span to the disordered speakers, to allow comparisons in performance. Results: Repeated measures analysis of variance was used to evaluate changes accompanying treatment. Significant time by group interactions for /aI/F2 slope, /eI/F2 slope, sample duration, and speaking time ratio were observed. As compared to the controls, diphthong second formant transitions increased in slope, and timing measures showed increases in speech continuity for the speakers with MTD. Conclusions: Collectively, these preliminary findings suggest that individuals with MTD experience changes in both articulatory and phonatory behavior following successful treatment that targets the larynx. Reprinted by permission of the publisher.